2023
DOI: 10.1093/mnras/stad923
|View full text |Cite
|
Sign up to set email alerts
|

The role of previous generations of stars in triggering star formation and driving gas dynamics

Abstract: We present hydrodynamic and magnetohydrodynamic (MHD) simulations of sub galactic regions including photoionising and supernova feedack. We aim to improve the initial conditions of our region extraction models by including an initial population of stars. We also investigate the reliability of extracting regions in simulations, and show that with a good choice of region, results are comparable with using a larger region for the duration of our simulations. Simulations of star formation on molecular cloud scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…Of particular interest is the concept of positive SN feedback or triggered star formation, where a strong shock wave compresses the gas, leading to further collapse, fragmentation and eventually the formation of new stars. This process has been predicted in numerous theoretical works (e.g., Dwarkadas et al 2017;Krause et al 2018;Herrington et al 2023), and it has recently been confirmed with observations from the Gaia mission (e.g., Miret-Roig et al 2022;Zucker et al 2022;Ratzenböck et al 2023).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Of particular interest is the concept of positive SN feedback or triggered star formation, where a strong shock wave compresses the gas, leading to further collapse, fragmentation and eventually the formation of new stars. This process has been predicted in numerous theoretical works (e.g., Dwarkadas et al 2017;Krause et al 2018;Herrington et al 2023), and it has recently been confirmed with observations from the Gaia mission (e.g., Miret-Roig et al 2022;Zucker et al 2022;Ratzenböck et al 2023).…”
Section: Introductionsupporting
confidence: 75%
“…Many aspects of galaxy formation and evolution, like star formation and the modeling of galactic outflows (e.g., Fielding et al 2017;Orr et al 2022), are tightly linked to the evolution of supernova remnants (SNRs). SNe are believed to maintain the hot phase (e.g., de Avillez & Breitschwerdt 2004;Bieri et al 2023), drive turbulence and outflows (e.g., Rosen & Bregman 1995;Fielding et al 2018;Krumholz et al 2018;Oku et al 2022), regulate the star formation rate in disk galaxies (e.g., Shetty & Ostriker 2012;Shimizu et al 2019;Herrington et al 2023), and enrich their surroundings with heavy elements and dust (e.g., Kozasa et al 1989;Bianchi & Schneider 2007;Nozawa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It seems likely that both play a role, e.g. photoionisation initially creates cavities and shapes the gas but this is further accentuated by supernovae (Rogers and Pittard, 2013;Grudić et al, 2022;Herrington et al, 2023). The current literature seems to find that on larger scales supernovae and ionisation are dominant compared to winds (Marinacci et al, 2019;Ali et al, 2022) and radiation pressure (Marinacci et al, 2019).…”
Section: Feedbackmentioning
confidence: 99%
“…Spiral arms are also able to induce velocity dispersions in the spiral arms, both from the shock Dobbs and Bonnell, 2007), and tidal forces acting over larger scales along the spiral arm (Falceta-Gonc ¸alves et al, 2015). Most consensus however points towards supernovae driving velocity dispersions of several km s −1 up to 100 − 200 pc scales (Slyz et al, 2005;Dib et al, 2006;Joung and Mac Low, 2006;Dobbs et al, 2011a;Hill et al, 2012;Gent et al, 2013;Lu et al, 2020;Herrington et al, 2023). There is still some debate though whether feedback alone drives turbulence, and whether feedback or gravity is the source of the shape of the velocity power law spectrum.…”
Section: Turbulent Drivingmentioning
confidence: 99%
“…How stellar feedback from outflows, H II regions and stellar winds from formed OB protostars influences the formation of new generation of stars and reshapes gas distribution in clouds is highly debated (e.g., Krumholz et al 2014;Peters et al 2017;Schneider et al 2020;Zhang et al 2023b;Herrington et al 2023;Pouteau et al 2023). The ATOMS survey studied the impact of UC H II regions (S. Zhang et al 2023, in preparation) on their surrounding molecular gas, but detailed investigation was limited by sensitivity, and resolution.…”
Section: Scientific Objectives Of the Quarks Surveymentioning
confidence: 99%